2021
DOI: 10.2196/27531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asynchronous Electronic Communication–Based Visits on Clinical Outcomes and Health Care Delivery: Systematic Review

Abstract: Background Electronic visits (e-visits) involve asynchronous communication between clinicians and patients through a secure web-based platform, such as a patient portal, to elicit symptoms and determine a diagnosis and treatment plan. E-visits are now reimbursable through Medicare due to the COVID-19 pandemic. The state of evidence regarding e-visits, such as the impact on clinical outcomes and health care delivery, is unclear. Objective To address this gap, we examine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 74 publications
0
22
0
7
Order By: Relevance
“…10 Regarding clinical outcomes, evidence indicates that telemedicine is at least as effective as face-to-face care across several mediums, diseases, and medical specialties including primary care. [11][12][13][14][15] CDSS have been found to positively affect practitioner performance. 16 Computerbased medical histories have been shown to be clinically relevant.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Regarding clinical outcomes, evidence indicates that telemedicine is at least as effective as face-to-face care across several mediums, diseases, and medical specialties including primary care. [11][12][13][14][15] CDSS have been found to positively affect practitioner performance. 16 Computerbased medical histories have been shown to be clinically relevant.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…17 However, for all areas, evidence of higher quality is needed. [11][12][13][14][15][16][17] For artificial intelligence in primary care, clinical applications and research are under rapid development but also raise concerns. [18][19][20][21] New digital environments can be challenging for patients and caregivers alike, requiring continuous learning and adjustment.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Though the pandemic led to regulatory revisions permitting reimbursement for asynchronous care [ 8 ], policymakers and practitioners have maintained reservations, particularly in direct-to-consumer (DTC) scenarios where care is commonly delivered asynchronously but patients and providers do not have a preexisting relationship [ 2 , 9 ]. This hesitation is justified given the limited evidence on whether telemedicine can lead to inappropriate prescribing and increased risk of failing to identify factors that might contribute to increased side effects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, another study comparing these modalities found that asynchronous care might create conditions that could negatively impact patient safety: providers adopted different prescribing behaviors depending on the modality of treatment for otherwise similar patients [ 13 ]. A recent literature review identified only 19 studies that quantitatively evaluated e-visits and concluded that while they appeared to result in similar health outcomes as compared to in-person care, evidence on quality outcomes is mixed, and there were no included studies comparing them to telephone or video visits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A patient portal is an internet-based application combining knowledge and software tools [ 18 , 19 ] that allow patients to have autonomous access to their electronic health record (EHR) anywhere at any time [ 20 , 21 ]. Besides its core function of providing EHR access [ 22 ], the features of a patient portal range from viewing visit notes, requesting medication refills, appointment scheduling, access to test and lab results, secure messaging with the health provider, e-visits, or reporting patient-generated health data [ 17 , 23 - 26 ]. Patient portals are used in different organizational settings such as independent physician practices and hospitals, group practices, or large, integrated health care delivery organizations [ 27 - 29 ].…”
Section: Introductionmentioning
confidence: 99%